Social ties of Lithuanian students: A diagnostic research, using the matrix of a social network - Antinienė, Dalia; Baršauskienė, Viktorija; Merkys, Gediminas (Psichologija, 2004)
The given article analyses the definition of a social network and its treatment, discusses the tradition of empirical research, schools, as well as several contemporary studies. It also reveals the functional (applied) significance of social network research and conceptions.At present the social network has been analysed on different levels: individual, group, community, etc. However, the preferred methods are the ones that mark the individual’s establishment in the social structure, as well as the formation of this structure from separate micro-ties. Consequently, the research prioritizes egocantered (personal) network that is oriented towards a separate individual, or an ‘individual – individual’ relationship.Different scientists, especially in the West, carry out numerous social network research exploiting various methodologies. According to the authors of this article, diagnostic social network research is considered to be most advanced. Subsequently, one of research objectives was to initiate the modelling of a more reliable, valid, and economical instrument that would allow an overall evaluation of a definite person or group social network.The article presents the data of the Lithuanian students’ social network empirical research. The research instrument is the social network matrix that is comprised of 35 items. The answer table was filled in by 305 young adults at different Lithuanian universities, colleges, and higher educational institutions. The matrix involves 7 social network subjects, namely, parents, siblings, spouses, friends, relatives, neighbours, schoolmates, and 5 social network functions, such as financial support, accommodation, emotional (or similar) support. Two structures of the social network were revealed in this research. These are the close medium, involving parents, spouses, siblings, and friends, and the distant medium, involving schoolmates, neighbours, and relatives. Based on the Multi-Dimensional Scaling model, as well as on the other indices, the article presents several arguments for the matrix constructional validity. The asymmetrically marked domineering of the financial support function is evident. It might be explained in the terms of specificity of the student population, or the social and economic conditions in Lithuania. Empirically defined network structure is treated as culturally specific, and is tried to be interpreted in the context of materialistic and post-materialistic value theory and modernization concept. There emerged particular hypotheses that require more detailed cross-cultural studies.After the norming base has been supplied, the method of the social network matrix could be treated as an independent diagnostic instrument in the future. For this reason the authors of this article are ready to provide all interested researchers with the informatikon necessary for norming and correct intercultural comparison.
Keywords: social ties